Sustained but Not Transient Phytochrome A Signaling Targets a Region of an Lhcb1*2 Promoter Not Necessary for Phytochrome B Action - Cerdán, Pablo D. (American Society of Plant Physiologists, 2000)
Current evidence is inconclusive regarding the point of signaling convergence downstream from different members of the phytochrome family. In transgenic Arabidopsis, the activity of a reporter enzyme under the control of the −453 to +67 fragment of an Lhcb1*2 promoter shows very low fluence responses (VLFRs) and high-irradiance responses (HIRs) mediated by phytochrome A and low-fluence responses (LFRs) mediated by phytochrome B. A 5′ deletion of the promoter to −134 abolished the HIR without affecting VLFR or LFR. In transgenic tobacco, VLFR and LFR were observed for the −176 to −31 or −134 to −31 fragments of Lhcb1*2 fused to 35S cauliflower mosaic virus minimal promoters, but only the largest fragment showed HIR. We propose that sustained activation of phytochrome A with far-red light initiates a signaling cascade that deviates from phytochrome B signaling and transient phytochrome A signaling and that this divergence extends as far as the Lhcb1*2 promoter.